Penerapan Model Pembelajaran Project Based Learning Pada Mata Pelajaran PAK Di SMA Kota Palangka Raya - Agnes Tri Ekatni; Fransiskus Janu Hamu; Agnes Angi Dian Winei (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
This research aims to describe the learning model used in the ongoing implementation of PAK. To demonstrate the roles of teachers and students in PAK learning using the project-based learning model. To implement the Project Based Learning model in the Catholic Religious Education subject at SMAN 1, 2, and 4 Palangka Raya. The method used in this research is qualitative descriptive research with data collection through observation, interviews, and documentation. The data analysis follows Miles and Hubermans three stages: Data Reduction, Data Display, and Conclusion Drawing. The participants in this study are seven individuals, including four Catholic religion teachers and three Catholic students. The research was conducted in June and July at SMAN 1, 2, and 4 Palangka Raya, Palangka Raya City. This research concludes that Catholic Religious Education (PAK) teachers at SMAN 1, 2, and 4 Palangka Raya have implemented the project-based learning model, and the student informants have applied the PJBL model throughout their learning process at their respective schools. The collaboration between teachers and students in implementing the PJBL model fosters good communication and teamwork. These efforts help students develop a positive attitude toward their teachers and vice versa. Implementing the PJBL model provides a positive overview for students in Palangka Raya in the Catholic Religious Education subject, incorporating PJBL steps that aid critical thinking and nurture creativity. The attitude integrates technology, resulting in engaging materials such as graphic designs like posters, PPTs, and instructional videos.